War by land, sea, and air : Dwight Eisenhower and the concept of unified command - Jablonsky, David (Yale library of military history., 2010)
"In this book a retired US Army colonel and military historian takes a fresh look at Dwight D. Eisenhower's lasting military legacy, in light of his evolving approach to the concept of unified command. Examining Eisenhower's career from his West Point years to the passage of the 1958 Defense Reorganization Act, David Jablonsky explores his efforts to implement a unified command in the US military. This key concept eventually led to the current organization of the Joint Chiefs of Staff and, almost three decades after Eisenhower's presidency, played a major role in defense reorganization under the Goldwater-Nichols Act. In the new century, Eisenhower's approach continues to animate reform discussion at the highest level of government in terms of the interagency process."--Jacket